Spatial differentiation of agricultural water resource utilization efficiency in the Yangtze River Economic Belt under changing environment. (20th April 2022) - Shi, Changfeng; Li, Luji; Chiu, Yung-Ho; Pang, Qinghua; Zeng, Xinyun
Abstract: With the change of environment and the rapid development of economy, the problems of low effective utilization rate and uneven spatial distribution of agricultural irrigation water in the Yangtze River Economic Belt (YREB) are becoming increasingly prominent. This paper takes precipitation as an environmental exogenous variable into the measurement of water resource utilization efficiency. Data Envelopment Analysis (DEA) window model is applied to evaluate the agricultural water resource utilization efficiency（AWUE） of the YREB from 2010 to 2019 while Social Network Analysis (SNA) method is used to explore characteristics of the spatial network correlation. The conclusions are as follows: (1) In terms of AWUE, it showed a fluctuating development trend of first rising and then falling, rising with time under the change of precipitation during 2010–2019. However, it did not achieve the effectiveness of DEA in general, and AWUE still had the potential and room for improvement. (2) From the perspective of spatial network structure, the overall network density of spatial correlation of agricultural water resource utilization efficiency showed an evolutionary trend of first increasing then decreasing. The agricultural water resource utilization efficiency among provinces and cities had significant but relatively loose spatial correlation, but the spatial relationship was relatively loose. Based on the research results, this paper puts forward relevant policy suggestions from the aspects of promoting agricultural water-saving technology innovation, giving full play to the role of macro-control and market mechanism, and strengthening the connection among the upstream, middle and downstream regions of the YREB, so as to promote the improvement of AWUE and coordinated development of the YREB.